2020
DOI: 10.3389/fonc.2020.01005
|View full text |Cite
|
Sign up to set email alerts
|

Mendelian Randomization Study: The Association Between Metabolic Pathways and Colorectal Cancer Risk

Abstract: Background: The roles of obesity-related biomarkers and their molecular pathways in the development of postmenopausal colorectal cancer (CRC) have been inconclusive. We examined insulin resistance (IR) as a major hormonal pathway mediating the association between obesity and CRC risk in a Mendelian randomization (MR) framework. Methods: We performed MR analysis using individual-level data of 11,078 non-Hispanic white postmenopausal women from our earlier genome-wide association study. We identified four indepe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 47 publications
(61 reference statements)
1
10
0
Order By: Relevance
“…Mendelian randomization (MR) is an epidemiological method, which uses genetic variants to evaluate the effect of exposure (e.g., coffee consumption) on an outcome (e.g., prostate cancer risk) [ 11 ]. Since the genetic variants are assorted randomly during gamete formation and mostly independent from environmental or lifestyle factors, MR is less vulnerable to the biases from reverse causation and confounding.…”
Section: Introductionmentioning
confidence: 99%
“…Mendelian randomization (MR) is an epidemiological method, which uses genetic variants to evaluate the effect of exposure (e.g., coffee consumption) on an outcome (e.g., prostate cancer risk) [ 11 ]. Since the genetic variants are assorted randomly during gamete formation and mostly independent from environmental or lifestyle factors, MR is less vulnerable to the biases from reverse causation and confounding.…”
Section: Introductionmentioning
confidence: 99%
“…The sample size of exposure and outcome ranged between 1475 and 898 130 and between 1475 and 706 031, respectively (Table S3). The causal factors can be classified into eight categories: anthropometric characteristics and obesity‐related biomarkers ( n = 31), 7–16 lifestyle habits ( n = 15), 9,10,17–21 blood micronutrients ( n = 36), 10,22–31 blood fatty acids (FAs) and lipids ( n = 43), 10,24,32–37 inflammatory biomarkers ( n = 14), 10,38–42 pathological conditions and related biomarkers ( n = 30), 10,43–50 reproductive factors ( n = 12), 10,51,52 and other biomarkers ( n = 9) 10,53–57 (Table 1, Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…three studies 46,47 but not in another, 10 and the largest one reported an OR (95% CI) of 1.11 (1.01-1.22). 47 Furthermore, no associations were found for a homeostatic model assessment for beta-cell function (HOMA-B), 45 homeostatic model assessment for insulin resistance (HOMA-IR), 48 glycosylated hemoglobin A1c (HbA1c), 45 HbA, 10 fasting glucose, 10,43,45,48 fasting insulin, 43,48 fasting proinsulin, 10 gallstone disease, 49 and bilirubin 49,50 (Table 1, Figures 2 and 3, Figure S6).…”
Section: Gallstonementioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, a meta-analysis has revealed that the homeostasis model of risk assessment-insulin resistance (HOMA-IR) was significantly associated with CRC risk [25]. In addition, a recent Mendelian randomization study pointed towards a potential causal relationship between genetically driven IR and CRC risk in postmenopausal women [26]. However, it should be noted that a retrospective study that used the National Health and Nutrition Examination Survey (NHANES) data [27] failed to demonstrate a significant difference in HOMA-IR between patients with and without CRC within a time frame of 5 years.…”
Section: Insulin Resistancementioning
confidence: 99%